2016
DOI: 10.4172/2161-1165.1000276
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Domestic Violence against Women in Iran: A Systematic Review

Abstract: Introduction: According to WHO suggestion, domestic violence against women is a health problem. Because of lack of information about general prevalence of domestic violence as well as contradiction among studies, this systematic review was performed to estimation of the prevalence of domestic violence against women by their husbands in Iran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…It is plausible that the higher education level can raise the awareness of partners of life skills, violence, and behavior management when confronting daily stressors (22). Moreover, men with higher education levels may provide better economic status for their family and it may be another reason for less IPV (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is plausible that the higher education level can raise the awareness of partners of life skills, violence, and behavior management when confronting daily stressors (22). Moreover, men with higher education levels may provide better economic status for their family and it may be another reason for less IPV (24).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that family financial level negatively affected IPV and unemployment was positively associated with IPV. Men's dissatisfaction with low and unstable economic situations can cause mental pressures or stress for men and thus affect IPV (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the types of violence against women is the most common type of domestic violence, with 90% of the victims of domestic violence being women [11]. According to the World Health Organization (WHO), in 2016, one-third women aged 15-49 were at risk of physical and sexual violence [13], which is in different regions, the WHO estimates the rate of violence in the Southeast Asian region was 38% [12]. In several studies in Iran that reported violence rates between 6% and 95% [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…According to the World Health Organization (WHO), in 2016, one-third women aged 15-49 were at risk of physical and sexual violence [13], which is in different regions, the WHO estimates the rate of violence in the Southeast Asian region was 38% [12]. In several studies in Iran that reported violence rates between 6% and 95% [13][14][15][16]. For example of this study, Hajnasiri et al (2016), the rate of violence in the whole country was reported by 66%.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the overall prevalence of IPV during marriage in Iran is estimated to be 66%, and 30% of those respondents experienced at least one act of serious physical violence in the course of their marriage (Vameghi, Khodaie Ardakani, & Sajjadi, 2013). A recent systematic review of physical violence against women in Iran reveals that the prevalence of physical IPV is as high as 23%, with the highest rates obtained in Tehran (Adineh, Almasi, Enayat Rad, Zareban, & Ansari Moghaddam, 2016).…”
mentioning
confidence: 99%